(untitled) (Journal of Economic Research & Business Administration, 2022)
The article examines the Chinese project “Silk Road Economic Belt” (SREB) from the standpoint of key risks and benefits for Kazakhstan. In this aspect, a characteristic is given of the New Silk Road, the possibility of using the republic’s potential for the implementation of the “One Belt, One Road” concept, the prospects for the development of cooperation between the PRC and the Eurasian Economic Union (EAEU). The relevance of the research topic is determined by the fact that Europe is intensively seeking access to Asian markets, and Asia is interested in the European market. The purpose, main directions and ideas of scientific research is to establish the risks and opportunities for Kazakhstan in the implementation of the Chinese SREB project. In the course of the study, it was found that for the Central Asian countries, cooperation between the EAEU and the SREB seems to be a new era of development for the entire Eurasian region. It can become a factor in economic growth, and for China – by improving the economic situation. Much attention is paid to the further development of transport potential and the formation of the logistics infrastructure of Kazakhstan, the development of oil and gas processing and the establishment of the chemical industry. Key words: Great Silk Road, “One Belt, One Road”, Economic Belt of the Silk Road, transport and logistics infrastructure, oil and gas processing, chemical industry.